Prácticas de autocuidado que realizan las mujeres con virus del papiloma humano - Gurrusquieta Borja, Ma. Trinidad (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
To analyze the practices of autocuidado that the women make with VPH. Methodology: The design of the investigation was of quantitative, cross-sectional and descriptive type with a sample of 30 women with clinical diagnosis of VPH that attended the clinic of displasias of the General Hospital Regional of Coyuca of Catalan, Guerrero, an instrument was applied whose structure was of 20 reagents of answer of multiple option and dichotomizing where the practices of autocuidado were evaluated with an analysis of reliability with Alpha de Crombach of .8109. Results: This way evidence that the VPH is one of the main problems that occur in the group of women of the second stage of the independent life of the social level of estatus. According to the results of the crossing of variables, applying the correlation of Pearson highly was a significant correlation (r=.625 p=.000) in the women with VPH that attend their appointment of medical checkup with the autocuidado practice of before the vaginal infections with one correlation (r=.625, p=.000). And en which talks about to that the women with VPH diagnosis are later made the cleanliness of the genitals before and of the sexual act (r=,552, p=.002) with the autocuidado practice of with the soap whereupon bathes they use it of individual form it has a strong correlation of (r=.552, p.002). Discussion: According to Coppard (1995) where she refers that the autocuidado one includes/understands strategies and decisions that a person takes directed to maintain and to improve the health to prevent, to diagnose and to treat her disease and to make decisions that lead the services of excellence health and to satisfy the necessities with the health. Conclusions: According to the obtained results of the square Chi of the variables that characterized like the cleanliness of the genitals, attendance of medical checkup and type of underclothes that use presenting/displaying a greater level of significance. Reason why in these data the hypothesis Has in virtue that is rejected the practices of autocuidado are efficient. Which was verified with the nonparametric tests.

Analizar las prácticas de autocuidado que realizan las mujeres con VPH. Metodología: El diseño de la investigación fue de tipo cuantitativo, transversal y descriptivo con una muestra de 30 mujeres con diagnóstico clínico de VPH que asistieron a la clínica de displasias del Hospital General Regional de Coyuca de Catalán, Guerrero, Se aplicó un instrumento cuya estructura fue de 20 reactivos de respuesta de opción múltiple y dicotómicas donde se evaluaron las prácticas de autocuidado con un análisis de fiabilidad con Alpha de Crombach de .8109. Resultados: De esta manera se evidencia que el VPH es uno de los principales problemas que se da en el grupo de mujeres de la segunda etapa de la vida independiente del nivel de estatus social. De acuerdo a los resultados del cruce de variables, aplicando la correlación de Pearson se encontró una correlación altamente significativa (r=.625 p=.000) en las mujeres con VPH que asisten a su cita de control médico con la práctica de autocuidado ante las infecciones vaginales con una correlación (r=.625, p=.000). Y en lo que se refiere a que las mujeres con diagnóstico de VPH se realizan el aseo de genitales antes y después del acto sexual (r= .552, p=.002) con la práctica de autocuidado con el jabón con que se baña lo utilizan de forma individual tiene una fuerte correlación de (r=.552, p.002). Discusión: Según Coppard (1985) donde refiere que el autocuidado comprende estrategias y decisiones que toma una persona dirigidas a mantener y mejorar la salud para prevenir, diagnosticar y tratar su enfermedad y tomar decisiones que conduzcan los servicios de salud de excelencia y satisfacer las necesidades de la salud. Conclusiones: De acuerdo a los resultados obtenidos de la Chi cuadrada de las variables que caracterizaron como el aseo de genitales, asistencia de control médico y tipo de ropa interior que usan presentando un mayor nivel de significancia. Por lo que en estos datos se rechaza la hipótesis Ha en virtud de que las prácticas de autocuidado son eficientes. Lo cual se comprobó con las pruebas no paramétricas.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2008-0007; Virus; Papiloma humano; Infección; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5615